PENERAPAN MEDEL PEER-REVIEW DALAM MEMBANGUN KETERAMPILAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA DI SEKOLAH DASAR NEGERI 109/II DESA MANGGIS - Pitriyani; Meli Yanti; Ahlia Ramadini; Dea Rahmadona; Rahmat Reziq Ramadhan; Sugeng Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to describe the implementation of the peer-review model in developing students’ skills in writing observation report texts at SD Negeri 109/II Desa Manggis. The study was motivated by the low level of students’ writing skills, particularly in generating ideas, organizing sentences systematically, selecting appropriate vocabulary, and applying proper language conventions in writing observation report texts. This research employed a qualitative approach with a descriptive qualitative design. The research participants consisted of teachers and students involved in learning activities related to writing observation report texts. Data were collected through observation, interviews, and documentation, while data analysis followed the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that students’ writing skills still required intensive guidance, especially in idea development and vocabulary use. The implementation of the peer-review model was carried out through several stages, including teacher instruction, writing activities, exchanging written work among students, providing feedback by peers, and reinforcement from the teacher. Students generally showed positive responses toward the peer-review model, as reflected in their enthusiasm and active participation during the learning process. The peer-review model was found to improve the quality of students’ writing through revision processes based on feedback from both peers and teachers. In addition, the model enhanced students’ learning motivation, self-confidence, critical thinking skills, and collaborative abilities. The challenges encountered during the implementation included limited vocabulary, low reading interest, and differences in students’ writing abilities. These challenges were addressed through collaborative learning and continuous support from teachers and peers. Therefore, it can be concluded that the implementation of the peer-review model had a positive impact on students’ observation report writing skills and can serve as an effective alternative teaching strategy for improving writing literacy at the elementary school level.